Comprehensive diagnosis and therapy as a condition of speech therapy efficacy of child diagnosed with delayed speech development - Karowicz, Anna (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
In the times of a constant civilizational progress and a rapid development of medicine and related studies, treating the patient holistically has become necessary in many fields, including speech therapy. The aim of the article is to present the need for interdisciplinary cooperation of specialists such as laryngologists, neurologists, pedagogues, psychologists, orthodontists, ophthalmologists, SI therapists, physiotherapists, audiologists or phoniatrists. Six cases of children with delayed speech development were presented, in which an accurate diagnosis and effective therapy could not be established without consulting other specialists. Another conclusion drawn from the article is that it is essential give the speech therapists an interdisciplinary education. Relevant knowledge in the field of laryngology, pedagogy, orthodontics, physiotherapy, psychology (especially in the therapy of stuttering or selective mutism), sensory integration therapy etc. should become mandatory for speech therapist, who should stay open to interdisciplinary cooperation with other specialists and be careful not to overstep his competences.